2020
DOI: 10.3389/fonc.2020.581189
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes With First-Line PD-1/PD-L1 Inhibitor Monotherapy for Metastatic Renal Cell Carcinoma (mRCC): A Multi-Institutional Cohort

Abstract: Introduction: The treatment landscape of metastatic renal cell carcinoma has advanced significantly with the approval of combination regimens containing an immune checkpoint inhibitor (ICI) for patients with treatment-naïve disease. Little information is available regarding the activity of single-agent ICIs for patients with previously untreated mRCC not enrolled in clinical trials. Methods: This retrospective, multicenter cohort included consecutive treatment-naïve mRCC patients from six institutions in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Nivolumab has been tested as first-line monotherapy in the phase 2 studies of HCRN GU16-260 (NCT03117309) [98] and OMNIVORE (NCT03203473) [99], which produced modest results and had adverse effects similar to prior studies involving nivolumab. Retrospective experience with ICI monotherapy has reported similar outcomes [100]. While these are proof-of concept studies, they raise the question of whether ICI monotherapy is an effective treatment strategy.…”
Section: Ici Monotherapymentioning
confidence: 88%
“…Nivolumab has been tested as first-line monotherapy in the phase 2 studies of HCRN GU16-260 (NCT03117309) [98] and OMNIVORE (NCT03203473) [99], which produced modest results and had adverse effects similar to prior studies involving nivolumab. Retrospective experience with ICI monotherapy has reported similar outcomes [100]. While these are proof-of concept studies, they raise the question of whether ICI monotherapy is an effective treatment strategy.…”
Section: Ici Monotherapymentioning
confidence: 88%
“…These findings were later supported by sub-analyses of the papillary subgroup from KEYNOTE-427, where the response rate was 28.8%. It should be noted that in all of the reported cohorts, both retrospective and prospective, durable responses have been documented [22].…”
Section: Immune Checkpoint Blockade In Select Populations: Papillary Typementioning
confidence: 89%
“…Overall, the use of ICI monotherapy has a variable degree of efficacy in nccRCC across the included series. Some studies report outcomes in the range of what has been reported for the use of ICI monotherapy in the treatment of ccRCC [20,22,23] while others have poorer results [21,[24][25][26]. The expected efficacy of ICI monotherapy among ccRCC was considered to be near the one reported in CheckMate-025 (ORR 25%, mPFS 4.6 months; mOS 25 months) [5].…”
Section: • Ici Monotherapymentioning
confidence: 99%
“…Overall, the higher ORR percentages were obtained in patients with an unclassified histology, with values as high as 44.4-66.7% [18,25]. Unclassified RCC includes different types of tumors with different behaviors, which can possibly explain the variability of outcomes between studies, with a lack of response and an ORR of 0% obtained in some series with a low number of these tumors [24,26].…”
Section: Immune Checkpoint Inhibitors In Special Histologiesmentioning
confidence: 99%
See 1 more Smart Citation